2012
DOI: 10.1002/jsfa.5885
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of commercial aromatised vinegars: phenolic compounds, volatile composition and antioxidant activity

Abstract: On the basis of the results from the cluster analysis of cases, it can be concluded that the grouping responds more to the trademark of each vinegar than to the raw material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 53 publications
(87 reference statements)
3
9
0
Order By: Relevance
“…Extracts from grapes and other plants have bacteriostatic effects . Antioxidant activity was highly correlated with the presence of trans‐p‐coutaric acid, trans‐caftaric acid, 5‐hydroxymethylfurfural and furfural . VOCs such as 22 β‐ionone and α‐ionone, together with ethyl acetate esters, were some compounds recognized as typical of ripened raspberry fruits …”
Section: Resultsmentioning
confidence: 99%
“…Extracts from grapes and other plants have bacteriostatic effects . Antioxidant activity was highly correlated with the presence of trans‐p‐coutaric acid, trans‐caftaric acid, 5‐hydroxymethylfurfural and furfural . VOCs such as 22 β‐ionone and α‐ionone, together with ethyl acetate esters, were some compounds recognized as typical of ripened raspberry fruits …”
Section: Resultsmentioning
confidence: 99%
“…Also, Sato et al [67] reported in vitro and in vivo antioxidant prosperities of chlorogenic and caffeic acids. Furthermore, Cejudo-Bastante et al [68] reported antioxidant effect of caftaric acid. Moreover, Huang et al [69] stated that METH abusers have persistently higher systemic oxidative stress throughout early abstinence.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have examined the volatile compounds in vinegars to distinguish and classify them according to their raw material, production processes, and origin using different analytical methods coupled to gas chromatography (GC), such as headspace (HS) [12], solid-phase extraction (SPE) [2], solid-phase microextraction (SPME) [13,14], stir bar sorptive extraction (SBSE) [15,16], and headspace sorptive extraction (HSSE) [17]. Vinegars have also been differentiated by their polyphenol content by means of liquid chromatography [15,18] or spectroscopic techniques, such as infrared (IR) [19,20,21] or fluorescence [22], just to mention some of them.…”
Section: Introductionmentioning
confidence: 99%